Tüketici satın alma karar aşamasında marka bağımlılığı etkisi ve meyve suyu tüketicileri üzerine bir uygulama - Ersin, Meltem (My University, 1999)
THE SUMMARY OF THESIS NAMED THE EFFECT of BRAND LOYALTY DURING CONSUMER'S PURCHASE DECİSION andAN IMPLEMENTATION IN JUICE MARKET Day by day, most of the products are branded in FMCG markets therefore consumers face with many brand choices everyday. These brands are presented to consumers at the same time in their categories.Thus, consumers who are in purchase decision level, have difficulties to choose a brand. Psychological and social factors such as education, culture, attributes are important. Besides these factors, marketing factors such as price, product, placement and promotion, brand loyalty are as important as these factors too. Recently, lots of the companies attach important to branding their products to make difference .By using marketing tools, they try to be one step in front of the competitors. To be successful, the companies make investment to their brands to create brand loyalty. Instore activities, discounts or product varieties are part of these investments From the view of consumers, satisfaction after purchase, trust to a brand, expectations from a brand and company are very important in repurchasing.These repurchases depend on the relationship between companies and consumers. If a consumer is satisfied with the brand and repurchases it again, it may be told that there is a tendency to the brand. During purchase desicion if the consumer is front of the shell in sales point, the choices depend on several factors like price, package or promotions. So in the thesis, the effect of brand loyalty factor during consumer purchase desion level is aimed to search.To reach the aim some subjects were tried to explain.These are : the factors that effect consumer purchase decision, purchase behavings, purchase levels, brand and brand loyalty concepts, brand loyalty models, brand types, disadvantages and advantages of brand loyalty, brand , brand types....For implementation, juice market was choosen and the survey was asked to juice consumers.
Keywords: PAZARLAMA YÖNETİMİ; TÜKETİCİ TERCİHLERİ